A highly sensitive multiplex immunoassay for inflammatory cytokines in dried blood spots. Issue 6 (31st December 2020) - McDade, Thomas W.; Miller, Aaron; Tran, Tina T.; Borders, Ann E. B.; Miller, Greg
Abstract: Objectives: Inflammatory cytokines are key regulators of inflammation, but current measurement approaches require venous blood to quantify low circulating concentrations associated with chronic, low‐grade inflammation. This article describes a highly sensitive multiplex immunoassay protocol for the measurement of IL6, IL8, IL10, and TNFα in finger stick dried blood spot (DBS) samples. Methods: The protocol uses a multiplex electrochemiluminescent immunoassay platform. The following measures of assay performance were evaluated: reliability (inter‐assay percent coefficient of variation; %CV), precision (intra‐assay %CV), lower limit of detection (LLD), linearity of dilution, and agreement with results from matched plasma samples. Results: Analysis of three control samples across the assay range indicated an acceptable level of precision and reliability for each cytokine. Linearity of dilution returned average values that ranged from 104.1 to 127.6% of expected. Lower limits of detection for IL6, IL8, and IL10 were <0.5, and <1.0 pg/ml for TNFα. Level of agreement in results between matched DBS and plasma samples was high for all cytokines except for IL8. Conclusions: Finger stick DBS sampling provides a viable alternative to venipuncture for the quantification of IL6, IL10, and TNFα at low concentrations associated with chronic inflammation. The presence of red blood cells may interfere with the quantification of IL8 in DBS. In facilitating blood collection in nonclinical settings this method can advance scientific understandings of how social and ecological contexts shape immune function and health over the life course.